Pemanfaatan Ruang Terbuka Hijau di Rumah Susun Studi Kasus : Rumah Susun Kebon Kacang dan Bendungan Hilir I - Mariana, Yosica (Bina Nusantara University, 2014)
One solution for meeting the needs of habitable housing for people, especially the middle to bottom is vertical housing or flats, this makes the availability of residential demand is increasing. In the process of vertical residential development should not only be limited to the provision of the physical aspects of the building, but also must consider the availability of green open space, which is based on the Law of Indonesia no. 26 of 2007 on Spatial Planning. Provision of green open space in the flats environment are very essential since beside becoming a place for socializing, open spaces are also has ecological function as a water catchment. Therefore, the purpose of this study was to determine the relationship between the user and the activities undertaken in theuse of green open space in the flat. The methods of research used is descriptive method to provide an overview of the user involvement and activities undertaken in the use of green open space. The results showed that the use ofgreen open spaces tend to be widely used by housewives and children paticularly in the morning and in the afternoon. The actvities include social interaction, play, sit and exercise.